Ethanol Extract of Tamarind Fruit Increased Glomerular Area in Lead-Induced Wistar Rats - Desy Andari; Muhammad Naufal Alzaky; Isbandiyah (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Lead (Pb) exposure is associated with nephrotoxicity, particularly structural alterations of the glomerulus mediated by oxidative stress. Tamarind fruit (Tamarindus indica L.) contains antioxidant compounds and vitamin C that may help attenuate lead-induced renal alterations. This study aimed to investigate the effect of ethanol extract of tamarind fruit on the glomerular area of Wistar rat kidneys exposed to lead. This experimental study conducted a post-test only control group design using 20 male Wistar rats. All groups were induced with lead acetate at a dose of 10 mg/kg body weight/day for 14 days. Treatment groups received ethanol extract of tamarind fruit (TFE) at doses of 12.5, 25, and 50 mg/kg body weight/day. Glomerular area was assessed histologically, and data were analyzed using one-way ANOVA and PostHoc. The results showed a significant difference in glomerular area among groups (p < 0.05). Administration of TFE at a dose of 12.5 mg/kg body weight/day demonstrated a more favorable glomerular area compared to the lead-only group, whereas higher doses did not show additional improvement. These findings suggest that low-dose TFE may influence glomerular structural changes induced by lead exposure.